The sword of Shannara - Brooks, Terry (New York : Ballantine Books, 1977)
In spite of his protests that he is only an ordinary man and not a hero, Shea Ohmsford eventually accepts his role as the leader of his people in the struggle against the Lord of Evil.
"A Del Rey book.".
School Library Journal.
Wilson's Fiction.
Wilson's Senior High School.
6.2
Young Adult
Keywords: Elves -- Fiction; Shannara (Imaginary place) -- Fiction; Fairies -- Fiction; Shannara (Imaginary place) -- Fiction; Fantastic fiction; Fantastic fiction